Authentication and distinction of Shenmai injection with HPLC fingerprint analysis assisted by pattern recognition techniques - Xue-Feng Lu; Kai-Shun Bi; Xu Zhao; Xiao-Hui Chen (Elsevier, 2012)
In this paper, the feasibility and advantages of employing high performance liquid chromatographic (HPLC) fingerprints combined with pattern recognition techniques for quality control of Shenmai injection were investigated and demonstrated. The Similarity Evaluation System was employed to evaluate the similarities of samples of Shenmai injection, and the HPLC generated chromatographic data were analyzed using hierarchical clustering analysis (HCA) and soft independent modeling of class analogy (SIMCA). Consistent results were obtained to show that the authentic samples and the blended samples were successfully classified by SIMCA, which could be applied to accurate discrimination and quality control of Shenmai injection. Furthermore, samples could also be grouped in accordance with manufacturers. Our results revealed that the developed method has potential perspective for the original discrimination and quality control of Shenmai injection. Keywords: Shenmai injection, High performance liquid chromatography, Fingerprint, Pattern recognition